2019
DOI: 10.3126/njh.v16i2.26314
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Disease prevalence in Heart Failure with Reduced Ejection Fraction

Abstract: Background and Aims: Even though heart failure (HF) is a major global health problem, studies on the prevalence and etiology of HF in Nepal are scant. Coronary artery disease (CAD) has been reported to be the etiology in 18% of HF presentations to the emergency department of a tertiary cardiac center in Nepal1. Present study evaluated the prevalence and characteristics of CAD in HF with reduced ejection fraction (HFrEF) with coronary angiography (CAG). Methods: In a prospective, observational study, cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…13 If taken that also our prevalence of CAD having stenosis >70% was 27% that closely matches with the descriptive studies from Nepal suggesting almost one-third of HFrEF are likely due to obstructive CAD (ischemic). 3,6,7 We further analyzed the forty-five cases with significant CAD (i.e stenosis >50%) for the involvement of coronary arteries where 20 (45%) were having triple vessel disease (TVD), 14 (32%) were having double vessel disease and 11 (23%) were having single vessel disease as shown in Figure 1. Individual assessment of coronary vessels showed involvement of LAD in 25 (55.5%), RCA in 12 (26.6%), and LCX in 8 (17.8%) cases (as in Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…13 If taken that also our prevalence of CAD having stenosis >70% was 27% that closely matches with the descriptive studies from Nepal suggesting almost one-third of HFrEF are likely due to obstructive CAD (ischemic). 3,6,7 We further analyzed the forty-five cases with significant CAD (i.e stenosis >50%) for the involvement of coronary arteries where 20 (45%) were having triple vessel disease (TVD), 14 (32%) were having double vessel disease and 11 (23%) were having single vessel disease as shown in Figure 1. Individual assessment of coronary vessels showed involvement of LAD in 25 (55.5%), RCA in 12 (26.6%), and LCX in 8 (17.8%) cases (as in Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…7,14,15 One study from central Nepal had shown significant CAD in only 33% of patients. 3 This is because the investigator had taken stenosis >70% as significant. In our study, only 27% of patients had obstructive CAD (stenosis >70%) which and 73% in patients with risk factors of 3 or more) as shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations